Pervaporative Separation of Mixed Volatile Fatty Acids: A Study Towards Integrated VFA Production and Separation - TUĞTAŞ KARNABAT, ADİLE EVREN; YEŞİL, HATİCE (SPRINGER, 2020)
Volatile fatty acids (VFAs) are heavily synthesized from fossil-based processes regardless of the scarcity of non-renewable resources. Anaerobic fermentation of organic wastes can be an alternative way to produce VFAs, however the recovery of VFAs from fermentation broths is the bottleneck of the resource recovery. In this study, membrane contactor based pervaporation system was used to recover VFAs through polytetrafluoroethylene (PTFE), tridodecylamine (TDDA) filled PTFE, and composite silicone rubber/PTFE membranes. Synthetic VFA mixtures were used as feed solutions representing fermentation broths composed of acetic, propionic, butyric, valeric, and caproic acids. Effect of temperature on recovery of VFAs through PTFE and TDDA filled PTFE liquid membrane was investigated at 21 degrees C, 35 degrees C, and 55 degrees C. In addition, effect of increased membrane thickness on VFA recovery efficiency of composite membranes was assessed at 35 degrees C. The results of the study revealed that TDDA filled PTFE liquid membrane resulted in significantly higher VFA flux, separation factor, permeance, and selectivity compared to that of PTFE membrane, which was presumably due to strong ion-pair formation between TDDA and carboxylic acids. The highest permeance of VFAs were observed at 35 degrees C through TDDA filled PTFE liquid membrane. Membrane thickness significantly influenced the VFA separation efficiency in composite membranes. The highest membrane selectivity of VFAs was observed in a composite membrane with 190.24.8 mu m thickness. The results of the study are significant in terms of the development of integrated fermentation and membrane-based VFA separation applications, which will hopefully decrease the reliance on fossil-fuels for VFA production.
Keywords: Carboxylic acids; Contactor; Membrane; Pervaporation; Recovery; ACETIC ACID/WATER MIXTURES; ORGANIC-ACIDS; FERMENTATION BROTH; CARBOXYLIC-ACIDS; AQUEOUS-SOLUTIONS; WASTE-WATER; ANAEROBIC FERMENTATION; HYDROGEN-PRODUCTION; BUTANOL PRODUCTION; AMINE EXTRACTANTS